Trade liberalization and regional integration: the search for large numbers - Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 1999)
The debate over the impact of regional trade agreements (RTAs) on world welfare hinges upon (1) whether they are net trade creating or trade diverting and (2) whether they impede multilateral trade liberalization. Theoretical models are ambiguous on these issues. We summarize the insights from the vast body of empirical literature on multi-country CGE models which analyze RTAs. The empirical models overwhelmingly show that aggregate trade creation dominates trade diversion. Indeed, in many cases, there is no absolute aggregate trade diversion from an RTA. The models also indicate that welfare for all members — both current and potential — increases when RTAs expand. There are even bigger welfare gains when models incorporate aspects of “new trade theory” such as increasing returns, imperfect competition, technology transfers, trade externalities, and dynamic effects such as links between trade liberalization, total factor productivity growth, and capital stock accumulation. We broaden the search for large numbers by suggesting an additional gain from RTAs. We conjecture that increases in intra-sectoral trade arise from the fact that an RTA provides an expanded secure market, and permits firms to pursue economies of fine specialization. This Smithian specialization in production is another source of efficiency gains.